Disparities in the Outcomes Following Ischemic Stroke Between the Floating Population and Indigenous Population of Shanghai - Liu, Xiaochuan; Sun, Qian; Yao, Sichen; Zhang, Junhui; Li, Huanyin (Frontiers in Neurology, 2021)
Abstract Background and purposes Through this study, we hope to gain more insights into the differences in outcome following ischemic stroke between the floating population and indigenous population of Shanghai. Method In this retrospective cohort study, we analyzed patients with first-ever acute ischemic stroke who were admitted to a comprehensive stroke center in the Minhang district, Shanghai from January 1st 2019 to December 31st 2020. All patients’ demographic data and medical histories were prospectively collected and they were followed up for at least three months. Indigenous population of Shanghai were defined as patients with an identification number starting with 310. All others were treated as the floating population. The primary outcome was defined as unfavorable prognosis at 3 months with a modified Rankin Scale (mRS) score above 1. Secondary outcomes included the use of emergency medical service (EMS), 3-h arrival rate, and the endovascular therapy in eligible patients. Logistic regression analysis was applied to investigate the differences. Results Finally, 698 patients with first-ever acute ischemic stroke were included (mean age, 65.32 years, 74.6% male). Of these, 302 patients belonged to the floating population group. Indigenous population with ischemic stroke were older than the floating population (68.26 years versus 61.47 years, P<0.001). The floating population was more likely to achieve favorable outcomes at 3 months compared with the indigenous population in multivariable logistic regression analysis (Odds ratio [OR] 0.49 95% Confidence Interval [CI] 0.32-0.75, P=0.001). The use of EMS, 3-h arrival rate, and the application of endovascular therapy were comparable between the floating population and indigenous population (OR 0.89 95% CI 0.62-1.27, P=0.519, OR 0.78 95% CI 0.56-1.09, P=0.146, and OR 0.82 95% CI 0.54-1.26, P=0.365, respectively). Conclusion Compared with indigenous population, the floating population with first-ever ischemic stroke was more likely to have a favorable outcome at 3 months.